PERAN UNICEF DALAM MENANGANI PEREKRUTAN TENTARA ANAK (CHILD SOLDIERING) DI MYANMAR (TAHUN 2007-2013) - Dorma Elvrianty Sirai; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research attempts to describe how UNICEF addressing one of humanrights issue, child soldiering, in Myanmar. Myanmar has the largest number ofchild soldiers in the world. These child soldiers not only use as combatant, butalso spies, porters, messengers, cooks, lay or clear landmines, training orguarding other childres, weapon transport workers, and even for sexual purposes.Use children in any purpose in military cause psychological, physical andsociocultural sufferings. Child soldiers are deprived of their basic andcontitutional fundamental rights such as their life, liberty, security and so forth.Method applied in this research is description, which trying to describehow an intergoventmental organization play its role in adrressing a global humanrights phenomenon.UNICEF work in 191 countries in the world in order to protect childrenand their fundamental rights which had written in Convention on the Rights of theChildren . UNICEF works in order to protect children from poverty, violence,disease, and discrimination. UNICEF has the main role in aim to end childsoldiering in the world, especially Myanmar.Keywords: Myanmar’s Child Soldiering, UNICEF, Conventional on the Rightsof the Children.